A comparative clinical study between laparoscopic-assisted vaginal hysterectomy versus nondescent vaginal hysterectomy in benign pathological conditions - Naveen Prasanna; Apoorva Menshi; Kavita Mahadevappa (MRIMS Journal of Health Sciences)
Background: The need of hour is an ideal hysterectomy surgery which has shorter operative time and shorter duration of hospital stay, early resumption to work, avoidance of disfiguring scar on abdomen, and less postoperative morbidities. Nondescent vaginal hysterectomy (NDVH) and laparoscopic-assisted vaginal hysterectomy (LAVH) are both minimally invasive surgeries with more benefits than total abdominal hysterectomy. Objective: To compare NDVH and LAVH in terms of operating time for surgery, intraoperative blood loss, intraoperative, and postoperative complications. Materials and Methods: A hospital-based prospective comparative study was carried out among 50 cases requiring hysterectomy. Detailed history was collected and thorough examination was conducted in 25 women who underwent LAVH and 25 women who underwent NDVH as per the standard operating guidelines. Parameters such as blood loss, duration of surgery, duration of hospital stay, intraoperative and postoperative complications, pain score, and time taken for ambulation were compared in the two groups. Results: Both the groups were comparable in terms of age, body mass index, comorbidities present, size of the uterus, past history of surgery, and diagnosis (P > 0.01). Both the groups were comparable for intraoperative or postoperative complications (P > 0.01). The mean blood loss, time taken for ambulation, pain score, and duration of hospital stay were significantly lesser (P < 0.01) in the LAVH group compared to the NDVH group even though the duration of surgery was significantly (P < 0.01) more in this group. Conclusion: We conclude that LAVH has more advantages over NDVH and should be incorporated in selected patients requiring hysterectomy.